Դավիթ եպս. Գեղամեցին գրի՞չ, թե՞ նոր սքանչելագործ միևնույն ձեռագրում (ՄՄ 3812, Հայսմավուրք) - Իրիցյան, Հասմիկ
The article discusses the issue of whether bishop David Geghamets‘i is the scribe of the Synaxarium Ms M3812, a matter complicated by the manuscript’s inclusion of a text entitled “The History of the Holy Bishop David Geghamets‘i, the New Wonder-worker” («Պատմութիւն սուրբ եպիսկոպոսին՝ Դաւթի Գեղամեցոյ նոր սքանչելագործին»). Bishop David Geghamets‘i was Armenian poet and ecclesiastical figure of the 16th-17th centuries. He is most known as the author of the poem “Lament for Jugha” («Ողբք ի Ջուղա») written in 1610. David Geghamets‘i is also known as a scribe. The manuscript M3812 was also copied in 1610 in the village called Gharamurat. In all likelihood, bishop David Geghamets‘i was also the illuminator of the manuscript. The scribe inserted the text in question after the entries of the Synaxarium, before the main colophon. Although in some published studies David Geghamets‘i is considered the scribe of the manuscript, the presence of this text in the manuscript raise doubts about whether this is true. It seems incredible that, in copying the Synaxarium, the scribe would insert his own biography among other saints and martyrs: describing himself as a “new thaumaturge”, “wonder-worker bishop,” and so on. Taking into account all the handwritten, documentary and other information, it is possible to conclude that David Geghamets‘i is both the scribe of the Ms M3812 and the character of the Life. The article also contains the text of “The Story of the Holy Bishop David Geghamets‘i, the New Wonder-worker” («Պատմութիւն սուրբ եպիսկոպոսին՝ Դաւթի Գեղամեցոյ նոր սքանչելագործին»). В статье рассмотрен вопрос, является ли епископ Давид Гегамеци писцом Синаксария М3812, если та же рукопись содержит текст под заглавием: «История святого епископа-нового чудотворца Давида Гегамеци». Епископ Давид Гегамеци – армянский поэт и церковный деятель XVI- XVII вв. Наиболее известнa его поэма «Плач по Новой Джульфе», написанная в 1610 г. Давид Гегамеци известен также как писец. Рукопись М3812 была создана в 1610 году в селе Гарамурад; по всей вероятности, Давид Гегамеци был также иллюстратором этой рукописи. Интересующий нас текст писец разместил сразу же после основных единиц Синаксария, перед главной памятной записью рукописи. Несмотря на то, что в нескольких опубликованных трудах Давид Гегамеци считается писцом этой рукописи, присутствие вышеупомянутого текста вызвало сомнение, так ли это на самом деле? Кажется невероятным, чтобы писец разместил свою биографию в им же переписанном Синаксарии, наряду с другими святыми, и называл бы себя «новым чудотворцем», «этим чудотворцем епископом» и т. д. Основываясь на рукописных, документальных и других сведениях, можно заключить, что Давид Гегамеци был и писцом рукописи, и характерным для Синаксария героем жития и чудотворцем. К статье прилагается текст «История святого епископа-нового чудотворца Давида Гегамеци».
Keywords: Պատմություն; Բանասիրություն